The Influence of MDR1 Expression Regulated by miR-138 through TRPS1 Signaling Pathway on Multidrug Resistance of Osteosarcoma and Formation of Bacterial Infection Biofilm: Influence of MDR1 on Multidrug Resistance of Osteosarcoma - Fang, Xiang; Zhu, Lizhen; Wu, Qiang; Zhong, Xueren; Chen, Yu; Zhu, Wengang (Cellular and Molecular Biology, 2023)
This study was to investigate the effect of microribonucleic acid (mi-RNA) on the resistance of human multidrug resistance gene 1 (MDR1) to osteosarcoma through the Trico-nasal finger syndrome 1 (TRPS1) pathway, as well as the effect of mi-RNA on biofilm formation. For this purpose, firstly, the expression of MDR1 and TRPS1 in osteosarcoma cells was detected by quantitative polymerase chain reaction (qPCR) technology. Moreover, the clinical paraffin sections of osteosarcoma cells were collected to explore the correlation between MDR1 and TRPS1. Then, both the MG-38 cells expressing and not expressing miR-138 were expanded. Afterward, a plasmid with a full-length clone of the TRPS1 antibody was applied to transfect the cells. Besides, Q-OCR was employed to detect the expression of TRPS1 and MDR1, and the expression of TRPS1 protein and P-glycoprotein (P-gp) was detected by Western blot (WB). The MTT method was adopted to detect the changes in the median lethal dose of doxorubicin and cisplatin in cells from each group. The well plate was used to establish an in vitro bacterial infection biofilm model, and the above two transfected cells were added during the model establishment process. Moreover, the formation of biofilm in the two groups was observed. The result of the paraffin biopsy was 33% (25/75) of mi-RNA, the positive rate of TRPS1 was 18.6%, and the Pearson correlation coefficient of the two was 0.477. Under mi-RNA interference, the TRPS1 and MDR1 of the three system cells were sharply reduced, and the trend of changes between the two was the same. The tolerance of the mi-RNA interference group to doxorubicin, cisplatin, paclitaxel and 5-fluorouracil decreased steeply, and the median lethal dose dropped, while the non-mi-RNA interference group showed the opposite trend. In addition, the number of colonies in the interference group was less sharp than that of the control group and the non-mi-RNA interference group. The conclusion was that mi-RNA could control the expression of MDR1 through the TRPS1 pathway, thus affecting the multi-drug resistance of osteosarcoma and also influencing the formation of bacterial biofilms.